Prevalence and Determinants of Intimate-Partner Violence among Pregnant Women Attending a City Health Centre IV, South western Uganda, during the COVID-19 Pandemic: A Cross-Sectional Study. - Katushabe, Eve; Chinweuba, Anthonia; Omieibi, Altraide; Asiimwe, John Baptist (Student's Journal of Health Research Africa, 2022)
Background: Intimate Partner Violence (IPV) during pregnancy is a significant public health problem worldwide and its impact on newborn outcomes is largely documented. Although conditions resulting from the COVID-19 pandemic have provided a perfect environment for IPV to thrive, the magnitude of IPV among pregnant women remains unclear. This study aimed to determine the prevalence and determinants of IPV during the COVID-19 pandemic among pregnant women in south-western Uganda. Methodology: This is a cross-sectional study of 345 pregnant women attending a large City Health Care facility consecutively enrolled. The validated WHO semi-structured women’s health and domestic violence questionnaire was used to identify women who had experienced IPV. Results: Of the 345 pregnant women, 67.5% experienced some form of IPV. The categories of IPV experienced by pregnant women included: controlling behaviors 188(80.6%), psychological 127(54.5%), sexual 84(36.1%), economic 99(42.5%), and physical violence at 33(9.6%). The most important predictor of all types of IPV experience was marital conflicts experience. Specifically, the predictors of psychological IPV experience were marital conflicts experience and emotional support from relatives. The strongest predictor of controlling behaviors IPV experience was marital conflicts experience. The strongest predictors of sexual violence IPV experience were decision-making, marital conflicts experience, pregnant women aged ≥35, and communicating with the family of origin. The predictors of economic IPV experience were decision-making, marital conflicts experience, financial support from relatives, and marriage duration. Conclusion: The IPV burden during the COVID-19 pandemic is widespread among pregnant women in south-western Uganda. Pregnant women reporting marital conflicts were more likely to experience IPV. These findings point to the need for integration of IPV screening in the routine ANC activities for every pregnant woman. Recommendations Health care providers need to identify and manage IPV as a health issue, not just as a societal matter if IPV is to be mitigated.